The ABBA project (Assess Better Before Access): A retrospective cohort study of neonatal intravascular device outcomes - van Rens, Matheus F. P. T.; Bayoumi, Mohammad A. A.; van de Hoogen, Agnes; Francia, Airene L. V.; Cabanillas, Irian J.; van Loon, Fredericus H. J.; Spencer, Timothy R. (Frontiers in Pediatrics, 2022)
Background: Vascular access devices (VADs) play a vital role within the neonatal intensive care unit (NICU). However, VAD-use is not without significant risks, with complications such as infection, thrombosis, device occlusion and infiltration/extravasation frequently contributing to device-related failures and increase the risk of significant patient harm or injury. Methods: A retrospective, cross-sectional, single-center study in a large 112-bed NICU in Qatar that routinely collected intravenous device data from January 2016 to December 2018 was evaluated. The outcome of interest was to identify and evaluate the relationships between unmodifiable and potentially modifiable factors and Assess the situation and patients Better Before initiating vascular Access (ABBA), potentially reducing unwarranted complication rates leading to therapy failure within the neonatal setting. Results: During the study period, 23858 VADs were inserted. Of these, 89.3% were peripheral intravenous catheters (PIVCs). Infants who received a peripheral device were slightly older, with a median age of 8 (5) days, when compared to all infants receiving a central device, with a median age of 6 (4) days. Univariate logistic regression analyses identified 10 variables demonstrating significant relationships to device-related outcomes. Conclusions: Four subgroups of VAD were identified (peripheral intravenous catheters, extended dwell-peripheral intravenous devices, peripherally inserted central catheters and umbilical venous catheters). Central vascular access (peripherally inserted central catheters and umbilical venous catheters) had the least reported complications. Future research toward improving patient and intravenous therapy-related outcomes plays an important role. It requires a focus on innovations and clinical advancements in the world of neonatology and vascular access devices.